2009
DOI: 10.1089/ten.tec.2008.0255
|View full text |Cite
|
Sign up to set email alerts
|

Manufacture of PLGA Multiple-Channel Conduits with Precise Hierarchical Pore Architectures and In Vitro/Vivo Evaluation for Spinal Cord Injury

Abstract: By the method of injection molding combined with thermally induced phase separation (TIPS), a novel nerve conduit with a plurality of channels and macro-/microporous architecture was fabricated using poly (lactide-co-glycolide) (PLGA, 75:25; Mn=1.22x10(5)). The diameter of the conduits and the number of channels could be regulated by changing the parameters of the mold, and the porosity of the conduit was as high as 95.4%. Meanwhile, the hierarchical pore architecture of the walls could be controlled through v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 37 publications
(50 reference statements)
1
60
0
2
Order By: Relevance
“…In our previous work, 22 we devised a protocol for the fabrication of poly(lactide-co-glycolide) (PLGA) multichannel conduits with hierarchical pore architectures, including 16 longitudinally aligned channels with 500-1000 mm diameters, 100-200 mm macropores, and 20-50 mm micropores. The method integrated low temperature injection, S-L phase separation, and salt-leaching technologies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous work, 22 we devised a protocol for the fabrication of poly(lactide-co-glycolide) (PLGA) multichannel conduits with hierarchical pore architectures, including 16 longitudinally aligned channels with 500-1000 mm diameters, 100-200 mm macropores, and 20-50 mm micropores. The method integrated low temperature injection, S-L phase separation, and salt-leaching technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the porosity was complementary to the ratio of the porous conduit weight to the theoretical solid conduit weight, the determination of the porosity for the three NCs was completed using the method described previously. 22 The porosity of the NCs includes two parts: the pores in the walls separating the open channels and the channels within the conduit. For the purpose of clarity, V s is defined as the volume of the whole conduit, V c as the volume of the channels, and V w as the volume of walls; D and d are the diameters of the conduit and channels, respectively; l is the length of the conduit; and the number 33 is the number of channels; m is the mass of NC; q is the density of PLLA, which was 1.25 mg/mm 3 .…”
Section: Characterization Of the Ncsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the matrix control also had better performance than non-treated control (one subject, scored 6), which indicated the physical support function of scaffold may help to reconstruct local disturbed circuits to regain function [52]. Animal studies with using PLGA and stem cells showed PLGA is an effective cell delivery scaffold with benign cytocompatibility and histocompatibility since it triggers mild immune/inflammation responses but facilitates seeded cells to integrate into host tissue after spinal cord injury [53,54].…”
Section: Poly (Lactic-co-glycolic Acid) (Plga)mentioning
confidence: 99%
“…As shown in Fig. 1, 17 studies were excluded for reasons such as the reports concerned only cell survival/feasibility studies, [44][45][46][47][48][49][50] preliminary or pilot studies, 44-60 the study was not specifically designed to study axonal regeneration after implantation of biopolymer based multimodality intervention, 56,[58][59][60] or a non-biodegradable implant was used in conjunction with the biodegradable scaffold. 55,57 The results are summarized in Table 1.…”
Section: Literature Reviewmentioning
confidence: 99%